The Development of MTs Miftahul Falah, 1987–2026: A Historical Analysis of Institutional Dynamics and Contributions to The Kebayoran Lama Community, South Jakarta - Ela Fadhlah; Abdul Rosyid Teguhdin Hamid (Manunggal Halim Jaya, 2026)
As an Islamic educational institution, a madrasah tsanawiyah (MTs) plays an important role in educating local communities and shaping their character. MTs Miftahul Falah is a private madrasah established on December 14, 1987, at Jalan Al-Mubarok II RT 02/10, Cipulir, Kebayoran Lama, South Jakarta, on waqf (Islamic endowment) land donated by Mrs. Siti Hawa. It was founded under Decree No. Wj/6-C/4994/1987, issued under the authority of the Ministry of Religious Affairs, and has maintained an A accreditation rating through two assessment cycles (Decree No. 326/BAP-S/M/DKI/2015 and Decree No. 1347/BAN-SM/SK/2021). Although the institution has operated for nearly four decades, its history and institutional dynamics have received little scholarly documentation. This study examines its founding, institutional development, and contributions to the surrounding community from 1987 to 2026. It uses a qualitative historical approach that combines official institutional records—the Ministry of Education's Basic Education Data system (Dapodik) and the Ministry of Religious Affairs' educational-unit database—with oral histories from in-depth interviews with five key informants: the founder, who also served as the first principal; the third principal, in office since 2019; one senior teacher; one alumnus; and one community leader. The data were analyzed using descriptive-historical analysis and source triangulation. The findings identify three phases of development: a pioneering phase (1987–2000), a development phase (2000–2015), and a modernization phase (2015–2026), each marked by changes in leadership, curriculum, and facilities. The madrasah has made significant educational, socio-religious, and local economic contributions and reflects the national pattern in which most Indonesian madrasah tsanawiyah are privately operated and sustained by community participation.